Long-term data from field erosion plot studies in eastern Austria - Andreas Klik (Data in Brief, 2020)
Soil erosion and runoff data are collected at three sites in eastern Austria using field erosion plots. Observed treatments include 1) conventional tillage with plough (CT), 2) mulch tillage with winter cover crop (MT), and 3) no-till with winter cover crop (NT). Data cover a time span from 1994 to 2018. They include data about surface runoff, soil loss, nitrogen, phosphorus and soil organic carbon losses as well as cop yields associated with the erosion processes. Interpretation of the data will be found in “Long-term experience with conservation tillage practices in Austria: impacts on soil erosion processes” [1].